2020
DOI: 10.1097/iae.0000000000002888
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Lapses in Treatment With Vascular Endothelial Growth Factor Inhibitors in Neovascular Age-Related Macular Degeneration in Routine Clinical Practice

Abstract: Purpose: Evaluating outcomes in patients receiving intravitreal antivascular endothelial growth factor (VEGF) inhibitors for neovascular age-related macular degeneration whom experience a lapse in treatment. Methods: A retrospective chart review evaluating 3,304 patients ≥18 years who experienced treatment lapses ≥3 months compared with control counterparts. Demographic information, macular thickness as measured by central subfield thickness, and visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
2
19
0
2
Order By: Relevance
“…Moreover, this study denoted that the time range to determine longlasting damages is brief, with the mean interruption length of 5 ± 3.7 months and a prevalent interruption length of 3-4 months. 23 Our results are in agreement with Stone et al, who reported that eyes with nAMD experienced the greatest loss of vision with treatment delay, and nAMD eyes were less likely to return to baseline on restarting treatment, indeed in this study 74.6% of nAMD patients returned to a BCVA within 5 letters of their baseline. 24 Sekeroglu et al report that visual acuity due to interruption was positively correlated with number of intravitreal anti-VEGF injections at last 6 months before COVID-19 pandemic and central subfoveal thickness at first post-COVID-19 visit; and negatively correlated with follow-up duration.…”
supporting
confidence: 93%
“…Moreover, this study denoted that the time range to determine longlasting damages is brief, with the mean interruption length of 5 ± 3.7 months and a prevalent interruption length of 3-4 months. 23 Our results are in agreement with Stone et al, who reported that eyes with nAMD experienced the greatest loss of vision with treatment delay, and nAMD eyes were less likely to return to baseline on restarting treatment, indeed in this study 74.6% of nAMD patients returned to a BCVA within 5 letters of their baseline. 24 Sekeroglu et al report that visual acuity due to interruption was positively correlated with number of intravitreal anti-VEGF injections at last 6 months before COVID-19 pandemic and central subfoveal thickness at first post-COVID-19 visit; and negatively correlated with follow-up duration.…”
supporting
confidence: 93%
“…Guidance to prioritise injections in those with nAMD is based on the known poor outcomes of these patients prior to the advent of anti-VEGF. Multiple studies have shown worsening VA and OCT features in patients who have anti-VEGF injections delayed [ 15 ], with some studies suggesting poor VA persisting on final follow-up despite normalisation of central foveal thickness after a period of delayed treatment [ 16 ]. Our study does support the belief that nAMD eyes do indeed seem to be most at risk of visual loss with delays in anti-VEGF treatment but also shows that RVO eyes have an increased risk from treatment delay.…”
Section: Discussionmentioning
confidence: 99%
“…57 Delays of 3 months or more in antivascular endothelial growth factor (VEGF) treatment were associated with persistently decreased visual acuities in patients with neovascular ARMD, even with resumption of treatment and return to baseline retinal thicknesses. 58 During the initial phases of the pandemic, many patients delayed seeking medical care, even for lifethreatening conditions like myocardial infarctions and cerebrovascular accidents. 59,60 Hospitals and outpatient clinics limited services to concentrate on combating COVID- 19 and decreasing viral transmission.…”
Section: Ophthalmic Clinical Services and Effects Of Delayed Carementioning
confidence: 99%